Complexities of local cultural protection in conservation: the case of an endangered African primate and forest groves protected by social taboos (2017)
Globally, some species and habitats receive protection through local belief systems (e.g. indigenous religions) and informal institutions (e.g. social norms and taboos). Where such systems represent the only form of protection for threatened species or environments, they may be critical to the survival of those taxa and sites. We evaluated the effectiveness of long-standing social taboos protecting the Endangered Sclater’s monkey Cercopithecus sclateri and forest groves in a community complex in Nigeria. Across its range (southern Nigeria), Sclater’s monkey is effectively protected only through informal institutions. At our study site, we conducted a census of the monkey population; measured the area of sacred groves; and compared our findings with estimates from  and , respectively. We observed a % increase in the monkey population (from  to  individuals) in a core survey area. No groves that we assessed in  had been fully cleared. Although we observed a decline in tree cover for several sacred forests, most groves used regularly by monkeys had changed little. The social taboos related to monkeys and sacred groves remain largely intact; however, other factors threaten the monkey population and remaining forests in this community complex, including the removal of tree patches to accommodate the construction of large residential buildings and the demand for cropland, as well as increased dumping of waste in forested sites. This study highlights the conservation importance and limitations of local cultural protection, as well as the challenges presented when such protection conflicts with community-perceived